A Novel Disturbance Rejection Control of Roll Channel for Small Air-to-Surface Missiles - Xiaomiao Ding; Yanpeng Hu; Ruilong Jia; Jin Guo (Applied Sciences, 2022)
In this paper, the issue of roll channel for attitude control for small air-to-surface missiles suffering from multiple disturbances is investigated. The dynamic model of roll channel is established and the roll controller of roll channel based on the active disturbance rejection control (ADRC) is designed. Based on the extended state observer, the disturbance is observed and compensated to track the roll rate accurately. Then, simulations and verification are carried out for rudder efficiency, barycenter location deviation, steering gear stuck, wind disturbance, drift error of inertial measurement unit (IMU) and other disturbances. The control effect is also compared with proportional integral derivative (PID) control and other ADRC algorithms. The results demonstrate that the algorithm has a good ability to suppress multiple disturbances. It can meet the control performance requirements of small air-to-surface missiles.